Bazedoxifene-induced vasodilation and inhibition of vasoconstriction is significantly greater than estradiol. Issue 2 (February 2019) - Zimmerman, Margaret A.; Hutson, Dillion D.; Mauvais-Jarvis, Franck; Lindsey, Sarah H.
Abstract: Objective: A new strategy for menopausal hormone therapy replaces medroxyprogesterone with the selective estrogen receptor modulator bazedoxifene. While the agonist or antagonist activity of bazedoxifene has been examined in other tissues, the current study explored the impact of bazedoxifene on resistance artery reactivity. We hypothesized that bazedoxifene may induce greater vasoprotective effects than estradiol due to enhanced activation of the G-protein-coupled estrogen receptor. Methods: We measured the vasodilation of mesenteric resistance arteries from adult male and female wild-type and G-protein-coupled estrogen receptor knockout mice (n = 58) in response to increasing concentrations of bazedoxifene, medroxyprogesterone, and estradiol, and also the impact of these compounds on the responses to phenylephrine and sodium nitroprusside. Results: Bazedoxifene-induced vasorelaxation was greater than estradiol and blunted phenylephrine-induced contraction—an effect not observed with estradiol. Neither estradiol nor bazedoxifene altered relaxation to sodium nitroprusside. The combination of bazedoxifene + estradiol promoted greater vasodilation than medroxyprogesterone + estradiol, and opposed phenylephrine-induced contraction, whereas medroxyprogesterone + estradiol failed to attenuate this response. Both bazedoxifene + estradiol and medroxyprogesterone + estradiol enhanced sodium nitroprusside-induced relaxation in females. Vascular responses were similar in both sexes in wild-type and G-protein-coupled estrogen receptor knockout mice. Conclusion: Bazedoxifene and bazedoxifene + estradiol relaxed mesenteric arteries and opposed vasoconstriction to a greater degree than estradiol or medroxyprogesterone + estradiol. These effects were independent of sex and G-protein-coupled estrogen receptor expression. We conclude that bazedoxifene may provide vascular benefits over estrogen alone or estrogen plus progestogen combinations in postmenopausal women. Abstract : Supplemental Digital Content is available in the text